2017
DOI: 10.1097/gme.0000000000000880
|View full text |Cite
|
Sign up to set email alerts
|

Visual improvements in vaginal mucosa correlate with symptoms of VVA: data from a double-blind, placebo-controlled trial

Abstract: Objective:To evaluate the response of the vaginal mucosa with TX-004HR and its correlation with vulvar and vaginal atrophy (VVA) symptoms, and whether visual examination is a useful measure for assessing VVA.Methods:REJOICE was a 12-week, phase 3, multicenter, randomized, double-blind, placebo-controlled study of a vaginal, muco-adhesive, 17β-estradiol softgel capsule (TX-004HR 4, 10, and 25 μg) in postmenopausal women with VVA and moderate-to-severe dyspareunia. Treatments were self-administered vaginally onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
(41 reference statements)
0
22
1
Order By: Relevance
“…6 VVA affects up to 63% of postmenopausal women 10,11 and can have a detrimental effect on the quality of life and sexual function of women. 4,11 Although VVA can be diagnosed with physical examination findings combined with patient-reported symptom history, 12 previous US patient surveys have reported that health care professionals (HCPs) rarely initiate the conversation on VVA symptoms and that a little more than half (54%e62%) initiate conversations with their patients about their VVA symptoms. 7,9 Although some women initiate the conversation, many do not volunteer or discuss their symptoms because they feel embarrassed, believe that nothing can be done, or that it might be an inappropriate topic to discuss with their HCP.…”
Section: Introductionmentioning
confidence: 99%
“…6 VVA affects up to 63% of postmenopausal women 10,11 and can have a detrimental effect on the quality of life and sexual function of women. 4,11 Although VVA can be diagnosed with physical examination findings combined with patient-reported symptom history, 12 previous US patient surveys have reported that health care professionals (HCPs) rarely initiate the conversation on VVA symptoms and that a little more than half (54%e62%) initiate conversations with their patients about their VVA symptoms. 7,9 Although some women initiate the conversation, many do not volunteer or discuss their symptoms because they feel embarrassed, believe that nothing can be done, or that it might be an inappropriate topic to discuss with their HCP.…”
Section: Introductionmentioning
confidence: 99%
“…The 10-cm visual analogue scale (VAS) used in our study has been proposed as a patient reported outcome in the draft guidance of medical product development to support labeling claims by the US Food and Drug Administration. 4 Moreover, the VAS has been used as a tool to assess GSM symptoms in many studies, assessing other treatment options for GSM such as lubricants, vaginal estrogens etc [5][6][7][8][9]. 2) The second comment of Digesu et al 1 relates to the microbiological assessment of the vaginal flora.…”
mentioning
confidence: 99%
“…Significantly more women using E2 had severity ratings of none to mild at week 12; vaginal color (79-84% vs 65% for placebo), vaginal epithelial integrity (83-89% vs 71%), vaginal epithelial surface thickness (78-83% vs 55%), and vaginal secretions (80-83% vs 61%) (all, p ≤ 0.0001 for each dose). All of these significant improvements were evident by week 2 [22]. Further, the sum of the individual visual assessment scores showed a significant linear correlation with the severity of dyspareunia and vaginal dryness at week 12 (both, p < 0.0001) [22].…”
Section: Visual Assessmentmentioning
confidence: 82%
“…All vaginal assessment parameters significantly improved from baseline to week 12 with all E2 doses versus placebo (Table 1) [22]. Significantly more women using E2 had severity ratings of none to mild at week 12; vaginal color (79-84% vs 65% for placebo), vaginal epithelial integrity (83-89% vs 71%), vaginal epithelial surface thickness (78-83% vs 55%), and vaginal secretions (80-83% vs 61%) (all, p ≤ 0.0001 for each dose).…”
Section: Visual Assessmentmentioning
confidence: 99%
See 1 more Smart Citation